Comparison of effectiveness and complications in trabeculotomy with phacoemulsification between ab externo and ab interno using a spatula-shaped microhook - Satoru Kanda; Takashi Fujishiro; Takashi Omoto; Ryosuke Fujino; Takahiro Arai; Yohei Nomoto; Makoto Aihara (Scientific Reports, 2021)
Abstract To compare the short-term surgical effectiveness and safety profile of trabeculotomy ab externo and ab interno with microhook in terms of the recovery of visual acuity. A retrospective chart review was performed on patients who underwent trabeculotomy combined with phacoemulsification and lens implantation at Asahi General Hospital, with 6 months of follow-up. The patients treated by trabeculotomy were classified into two groups depending on the surgical procedures: ab interno with Tanito microhook (TMH) and ab externo with rigid probe trabeculotome (LOT). The demographics, preoperative and postoperative intraocular pressure (IOP), number of medications (Med), best-corrected visual acuity (BCVA), surgical-induced astigmatism (SIA), and postoperative complications were analyzed at pre-operation, and 1 week and 1–6 months post-operation. Fifty-two eyes of 38 Japanese patients underwent TMH and 42 eyes of 32 patients underwent LOT. The decreases in IOP and Med from the baseline were significant at all time points in both groups (p < 0.001), but there were no significant differences between the two groups. BCVA improved significantly in TMH and LOT after the operation (p < 0.001). BCVA and SIA significantly improved, mostly at 1 week in TMH, compared with LOT (p = 0.02 and 0.003). Hyphema and IOP spike exceeding 30 mmHg (spike) occurred in 11% and 6% of participants in TMH, and 33% and 26% of participants in LOT, respectively. Hyphema and IOP spike occurred more frequently in the LOT than in the TMH group (p = 0.01 and 0.005). Ab interno trabeculotomy showed similar IOP-lowering effects as ab externo, but had less postoperative complications.